2016
DOI: 10.1111/odi.12429
|View full text |Cite
|
Sign up to set email alerts
|

Oral chronic GVHD outcomes and resource utilization: a subanalysis from the chronic GVHD consortium

Abstract: Oral cGVHD consensus assessments corresponding with ancillary therapy use were mouth pain and NIH mouth score, with higher odds ratios of receiving therapy from OM experts. Ancillary care guidelines for oral cGVHD are reflected in academic clinical practice with respect to utilization of recommended prescriptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
(29 reference statements)
1
1
0
Order By: Relevance
“…This practice is consistent with treatment approaches in other organs [69]. Data from cGVHD Consortium sites has confirmed that treatment behavior follows these recommendations with topical therapies more likely to be used in patients reporting pain and decreased oral function [70]. Follow-up is recommended to confirm symptom control and restoration of mucosal integrity.…”
Section: Oral Mucosal Cgvhdsupporting
confidence: 54%
“…This practice is consistent with treatment approaches in other organs [69]. Data from cGVHD Consortium sites has confirmed that treatment behavior follows these recommendations with topical therapies more likely to be used in patients reporting pain and decreased oral function [70]. Follow-up is recommended to confirm symptom control and restoration of mucosal integrity.…”
Section: Oral Mucosal Cgvhdsupporting
confidence: 54%
“…In the KSA, Aboalela et al reported oral GvHD in 30.6% of patients, identifying weight loss was more prevalent among oral GvHD, and oral mucositis was linked to significant weight loss [ 45 ]. Patients with OLL associated with GvHD undergo similar treatment as for OLP, but often require closer monitoring due to both the potentially malignant nature of OLL in combination with the risk of secondary malignancies arising as a complication of GvHD [ 46 ].…”
Section: Graft-versus-host Diseasementioning
confidence: 99%